Cancer-Associated Fibroblasts Connect Metastasis-Promoting Communication in Colorectal Cancer - Tommelein, Joke; Verset, Laurine; Boterberg, Tom; Demetter, Pieter; Bracke, Marc; De Wever, Olivier (Frontiers in Oncology, 2015)
Colorectal cancer progression and eventually metastasis is directed in many aspects by a circuitous ecosystem consisting of an extracellular matrix scaffold populated by cancer-associated fibroblasts (CAFs), endothelial cells and diverse immune cells. CAFs are recruited from local tissue-resident fibroblasts or pericryptal fibroblasts and distant fibroblast precursors. CAFs are highly abundant in colorectal cancer. In this review, we apply the metastasis-promoting communication of colorectal CAFs to ten cancer hallmarks described by Hanahan and Weinberg. CAFs influence innate and adaptive tumor immune responses. Using datasets from previously published work we re-explore the potential messages implicated in this process. Fibroblasts present in metastasis (metastasis-associated fibroblasts) from colorectal cancer may have other characteristics and functional roles than CAFs in the primary tumor. Since CAFs connect metastasis-promoting communication, CAF markers are potential prognostic biomarkers. CAFs and their products are possible targets for novel therapeutic strategies.